Evolving Face of Quality in The World Robotics Process Automation (RPA) - Kedar Argade; Krishna Madrewar (International Journal of Advanced Robotics and Automation Technology, 2023)
Robotics Process Automation (RPA) is a technology that automates repetitive and rule-based tasks using software robots or "bots." These bots mimic human interactions with digital systems and perform tasks like data entry, validation, report generation, and system integration. RPA leverages AI and ML to improve operational efficiency and can be applied across industries and functions. Implementing RPA offers benefits such as error reduction, productivity enhancement, and cost savings. RPA is not meant to replace humans but to augment their capabilities, enabling them to focus on strategic tasks. Advancements like cognitive automation combine RPA with AI technologies for handling unstructured data and performing sophisticated tasks. To implement RPA, organizations typically follow a few key steps. First, they identify the processes suitable for automation by assessing their volume, repetitiveness, and rule-based nature. Then, they design and develop the automation workflows, configuring the bots to perform the desired tasks. After testing and refining the automation, the bots are deployed in production, and their performance is continuously monitored and optimized. It's important to note that RPA is not meant to replace human workers but rather to augment their capabilities. By automating mundane and repetitive tasks, RPA enables employees to focus on more creative and complex activities that require human judgment and decision-making. As the field of RPA continues to evolve, new advancements such as cognitive automation (combining RPA with AI technologies like natural language processing and machine learning) are emerging. These advancements enable bots to handle unstructured data, make intelligent decisions, and perform more sophisticated tasks.
Keywords: Artificial Intelligence (AI); Automation; Bots; Robotics Process Automation (RPA); Software robots